Study of muon neutrino disappearance using the Fermilab Main Injector neutrino beam - Adamson, P; Andreopoulos, C; Arms, K; Armstrong, R; Auty, D; Avvakumov, S; Ayres, D; Baller, B; Barish, B; Jr, B; Barr, G; Barrett, W; et al. (2008)
We report the results of a search for νμ disappearance by the Main Injector Neutrino Oscillation Search. The experiment uses two detectors separated by 734 km to observe a beam of neutrinos created by the Neutrinos at the Main Injector facility at Fermi National Accelerator Laboratory. The data were collected in the first 282 days of beam operations and correspond to an exposure of 1.27×1020 protons on target. Based on measurements in the Near Detector, in the absence of neutrino oscillations we expected 336±14 νμ charged-current interactions at the Far Detector but observed 215. This deficit of events corresponds to a significance of 5.2 standard deviations. The deficit is energy dependent and is consistent with two-flavor neutrino oscillations according to |Δm2|=2.74-0.26+0.44×10-3eV2/c4 and sin 22θ>0.87 at 68% confidence level. © 2008 The American Physical Society.